Contexto, interacción y conocimiento en el aula - Correa Restrepo , Miralba (2022)
In the article a revision is made on the interactions that appear in the classroom and its relation with the processes of knowledge in the classroom. Dif ferent authors raise the importance of the context. This investigation is fundamental like element of reflection and analysis of the projection of the educative psychologist and the cognitive processes in the written composition. Additionally , one analyzes the active roll of educational and the student in the self-regulating procedures.